Gender Policing During Childhood and the Psychological Well-Being of Young Adult Sexual Minority Men in the United States. (May 2017) - Bauermeister, José A.; Connochie, Daniel; Jadwin-Cakmak, Laura; Meanley, Steven
Hegemonic masculinities (i.e., sets of socially accepted masculine behaviors and beliefs within a given time and culture) may affect the well-being of sexual minority men, yet quantitative relationships between these masculinities and well-being remain largely unexplored. Using data from a national cross-sectional survey of young sexual minority men ( N = 1, 484; ages 18-24 years), the current study examined the relationship between parental gender policing during childhood and adolescence and subsequent substance use and psychological distress. Over one third of the sample (37.8%) reported their parent(s) or the person(s) who raised them had policed their gender, including the use of disciplinary actions. Using multivariable regression, this study examined the relationship between parental gender policing and psychological well-being and substance use, after adjusting for age, race/ethnicity, educational attainment, and current student status. Gender policing during childhood and adolescence was associated with recent substance use behaviors and psychological distress in multivariable models. A linear association between substance use behaviors and psychological distress and the number of disciplinary actions experienced during childhood and adolescence was also observed. Parents' attempts to police their sons' gender expression were associated with markers of distress among young sexual minority men. The relationship between parental gender policing during childhood and adolescence and distress among young sexual minority men are discussed.